Understanding Mass Atrocity Prevention during Periods of Democratic Transition - McLoughlin , Stephen (2015)
The purpose of this article is to provide a better understanding of why some countries experience mass atrocities during periods of democratic transition, while others do not. Scholars have long regarded democracy as an important source of stability and protection from mass atrocities such as genocide, crimes against humanity and ethnic cleansing. But democratic transition itself is fraught with the heightened risk of violent conflict and even mass atrocities. Indeed, a number of studies have identified regimes in transition as containing the highest risk of political instability and mass atrocities. What is overlooked is the question of how and why some regimes undergo such transitions without experiencing mass atrocities, despite the presence of a number of salient risk factors, including state-based discrimination, inter-group tension and horizontal inequality. Utilizing a new analytical framework, this article investigates this lacuna by conducting a comparative analysis of two countries—one that experienced atrocities (Burundi) during transition, and one that did not (Guyana). How countries avoid such violence during transition has the potential to yield insights for the mitigation of risk associated with mass atrocity crimes.